2021
DOI: 10.3389/fphys.2021.651738
|View full text |Cite
|
Sign up to set email alerts
|

Time-Restricted Feeding in Commercial Layer Chickens Improves Egg Quality in Old Age and Points to Lack of Adipostat Activity in Chickens

Abstract: In mammals, time-restricted feeding (TRF) with no caloric restriction provides health benefits and extends longevity, usually with a minor (∼3%) or no reduction in total food consumption. In the current study, a TRF regimen of 6 h free access to food (08:00–14:00 h) was applied to Leghorn chickens from 25 to 86 weeks of age; control birds ate freely during the light hours (06:00–20:00 h). Unexpectedly, the TRF-treated birds consumed, on average, 11.7% less food than the controls. This was manifested by an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
3
10
0
1
Order By: Relevance
“…Overall, about 25% of the publications reviewed had laying rates in extended cycles falling below 70%—the laying rate that is considered a minimum threshold for commercial viability. The laying rates below 70% were seen mostly at 90 wk of age or beyond in the studies reviewed ( Saibaba et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, about 25% of the publications reviewed had laying rates in extended cycles falling below 70%—the laying rate that is considered a minimum threshold for commercial viability. The laying rates below 70% were seen mostly at 90 wk of age or beyond in the studies reviewed ( Saibaba et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interventions categorized under flock management were quite diverse. This category included studies on the effects of alternative feeding regimes ( Molnár et al, 2018a ; Saibaba et al, 2021 ), ambient temperature ( Tůmová and Gous, 2012 ), litter substrates, and molting ( Regmi et al, 2018 ). The most commonly addressed aspect under flock management, however, was the effect of housing type ( Anderson, 2012a , 2015 , 2018 ; Abo Ghanima et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the meat duck industry usually adopts a high-density and intensive rearing model, and excessive fat deposition in meat ducks, which affects the further development of the meat duck industry ( Na et al, 2019 ). In meat poultry production, restricted feeding ( RF ) was widely used to reduce lipid deposition in meat ducks ( Saibaba et al, 2021 ). Previous studies have shown that RF could affect growth performance, reproduction, and metabolic function of meat poultry, especially on lipid metabolism and deposition ( Pan et al, 2014 ; Mehus et al, 2021 ; Shusha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age is an important determinant of productivity in laying flocks (Holt, 2003;Tumova and Gous, 2012) influencing the health, and livability of individual birds as well as rate of lay, and egg quality (Tumova and Gous, 2012;Saibaba et al, 2021). When productivity becomes uneconomic due to aging, the farmer continues the enterprise by force moulting the flock to rapidly enter a second laying cycle (Aygun and Olgun, 2010;Wein et al, 2020) or by replacement of the flock.…”
Section: Introductionmentioning
confidence: 99%